PENGENDALIAN KUALITAS PANGAN DENGAN PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) PADA PROSES PRODUKSI DODOL BETAWI (STUDI KASUS UKM MC) - Rina Fitriana; Wawan Kurniawan; Jaquline Glenadys Siregar (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Small and medium enterprise (SME) MC is a business in food industri which produces dodol betawi. Problems in the production process is using human who aren’t yet familiar with the attributes of cooking equipment as well as proper guidance in food production process. Workers haven’t recognized yet the importance of employee hygine regarding physical and bacterial hazards from the body so it doesn’t contaminate the food. The purpose of this study is to analyze the discrepancy of SME MC in implementing Good Manufacturing Practice (GMP) regulations so that discussing higher safety on products using the Failure Mode and Effect Analysis (FMEA) method can improve dodol food quality, and provide quality improvement.Based in laboratory tests of dodol betawi products, there are Escherichia coli bacteria provide evidence that storage errors in the drying process, when dodol already 1 week old, it causes the fungus Aspergillus flavus growth. The amount of Escherichia coli bacteria was found 25.000 bacteria/cc. The purpose of this research is to give improvement of sanitation operations standards for employee health in the production process of Dodol Betawi by using one of the Hazard Analysis and Critical Control Point (HACCP) methods, namely the application of Good Manufacturing Practice (GMP). The implementation of Good Manufacturing Practices (GMP) in this research is to provide cooking attribute equipment. The results of the implementation were able to reduce Escherichia coli bacteria by 10,000 bacteria / cc. The results of these improvements are expected to be able to make the MC UKM more trusted and widely known to the public. Keywords: good manufacturing practice (GMP), failure mode and effect analysis (FMEA), laboratory test, quality food